A taxonomic review of the genus Callilanguria Crotch, 1876 (Coleoptera: Erotylidae: Languriinae) - Huang, Zheng-Zhong; Han, Xin-Yu; Yang, Xing-Ke (Zootaxa, 2018)
A worldwide review of the genus Callilanguria is presented. Three new species are described: C. weiweii Huang & Yang, sp. nov. from Sabah, Malaysia; C. helleri Huang & Yang, sp. nov. from Panay, the Philippines; and C. nigripes Huang & Yang, sp. nov. from Samar Island, the Philippines. Callilanguria scrupulosa Heller, 1918 is transferred to the genus Doubledaya. The other species are C. eximia Fowler, 1885; C. gorhami Villiers, 1945; C. asymmetrica Heller, 1900; C. ruficeps Achard, 1923; C. milloti Villiers, 1945; C. stenosoma (Harold, 1879); C. flaviventris Fowler, 1886; C. wallacii Crotch, 1876; and C. luzonica Crotch, 1876. In total, twelve species are recognized in the genus Callilanguria, and a key to the described species of the genus is provided.